VALUASI BISNIS PERUSAHAAN PT JAMINAN PEMBIAYAAN ASKRINDO SYARIAH DALAM RANGKA IPO DI TAHUN 2022 - Bunga Mareti Permatasari; Zulkifli Zulkifli; Syamsul Bahri (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
In order to absorb the potential of the sharia guarantee business in the future which will grow rapidly, PT Jaminan Pembiayaan Askrindo Syariah with the brand name "Askrindo Syariah" will carry out corporate actions, one of which is an initial public offering (IPO) in 2022. Askrindo Syariah's performance shows an increase in 5 years. However, Askrindo Syariah's business profile, which is mostly high-risk products, shows that the company's performance is not optimal even though it has increased. Accordingly, Askrindo Syariah needs to set a strategy in preparation for the IPO. The purpose of this study was to determine the business valuation of the company's strategy for Askrindo Syariah related to the initial public offering (IPO) plan in 2022. The results of the study show that the fair value range of share prices related to Askrindo Syariah's decision to carry out an IPO in 2022, based on the calculation of free cash flow to equity, the value of the company in 2022 is IDR 2,111,814 per share, while based on the relative valuation the book value is amounting to Rp 2,331,168,- per share. The results of this study can also determine the business valuation in 2025, the value of the company based on calculations using the FCFE method is Rp.2,929,706, - while based on the book value method is Rp.3,383,228,-. To maintain the company's value as projected, Askrindo Syariah needs to implement a company strategy to reach good underwritting quality product